Ecofascism: An Examination of the Far-Right/Ecology Nexus in the Online Space. Issue 5 (4th July 2022) - Hughes, Brian; Jones, Dave; Amarasingam, Amarnath
ABSTRACT: With Patrick Crusuis' 2019 attack that killed twenty-two people in El Paso, Texas, discussions of ecofascism were thrust into mainstream news outlets and magazines. In his manifesto, Crusius described himself as an "ecofascist" seeking to challenge the "environmental warfare" of immigration. His choice of target, a Walmart frequented by Mexican immigrants, reflects this ideological connection between ecological priorities and violent white supremacist ideology. In this paper, the authors provide a review of existing theoretical literature on ecofascism to identify its key characteristics, namely, its Romantic sensibilities, anti-humanism, and mysticism. The authors argue that these features distinguish ecofascism from what other scholars have deemed "far-right ecologisms." Following this, the authors draw on a larger corpus of data gathered from Twitter and Telegram between November 2019 and November 2020 to identify common themes in ecofascist circles, including the thinkers they frequently cite. The dataset examined shows notable differences in the types of content shared in ecofascist groups compared to the far-right more broadly.